Bird community responses to urbanization in a medium-sized argentine city: Santo Tomé (Santa Fe province) as a case study - Cristaldi, Maximiliano Ariel (2022)
Urbanization transforms the landscape and consequently affects biodiversity. Cities are heteroge-neous landscapes due to a differential distribution of human activities, infrastructure, and vegetation compo-sition. Bird assemblages vary according to such variations. In Argentina, assessments of the effect of urbanization on bird assemblages come from large capital cities, whereas in intermediate-size cities studies are scarce. Intermediate-size cities present higher growth rates than capital cities. Studies on the effect of Urban Land Uses (ULU) can contribute to the planning of urban growth. We evaluated the variation in taxonomic diversity of bird assemblages at different ULUs in Santo Tomé, an Argentine city of 66 133 inhabitants. We performed bird counts in seven ULUs (the centre, the suburban sector, the peri-urban sector, small urban parks, the mi-litary base, the riverside walkway, and the urban reserve). In each ULU, we located 10 transects of 100 m long x 50 m wide. In each transect we recorded bird species and their abundance and the number of pedestrians and vehicles. Taxonomic diversity varied among the different ULUs. The centre presented the lowest richness and diversity, in contrast to the highest values for these variables found in the riverside walkway and the urban reserve. The rest of the ULU presented intermediate levels of richness and diversity. The structure and composition of bird assemblages varied among ULUs. Our study reinforces the importance of ULU characterized by high vegetation cover, low levels of human activity, and with vegetation management for conservation purposes.